The effect of Microfinance on Poverty Reduction in Sindh: Study of District Khairpur Mir’s - Sohu, Zahid Hussain; Soomro, Hassan Jawad; Junejo, Mumtaz Ali; Lashari, Ali Raza (International Journal of Psychosocial Rehabilitation, 2020)
This research determines the role of microfinance to alleviate the poverty in District Khairpur. In this study effects of loan, income and education on poverty reduction were analyzed. A well structured and appropriate questionnaire was developed by me to collect primary data from 311 borrowers of microfinance banks. The data was analyzed by SPSS software. Correlation and regression techniques were applied to find out the results. The results showed the positive impact of loan, income and education upon poverty reduction. The research was limited only to Khairpur district and time period was short. The results of the study may vary keeping in the different areas owing to time constraints and utilization of loan.